De Novo Human Cardiac Myocytes for Medical Research: Promises and Challenges - Hamel, Veronique (Stem Cells Int, 2017)
The advent of cellular reprogramming technology has revolutionized biomedical research. De novo human cardiac myocytes can now be obtained from direct reprogramming of somatic cells (such as fibroblasts), from induced pluripotent stem cells (iPSCs, which are reprogrammed from somatic cells), and from human embryonic stem cells (hESCs). Such de novo human cardiac myocytes hold great promise for in vitro disease modeling and drug screening and in vivo cell therapy of heart disease. Here, we review the technique advancements for generating de novo human cardiac myocytes. We also discuss several challenges for the use of such cells in research and regenerative medicine, such as the immature phenotype and heterogeneity of de novo cardiac myocytes obtained with existing protocols. We focus on the recent advancements in addressing such challenges.